CONTEMPORARY CHALLENGES IN FRONT OF PARK DEVELOPMENT IN SOFIA (World Science, 2024)
The construction boom and the continuous migration to the city, as well as the ambition of the city administration to prevent the expansion of the physical boundaries of the city at the expense of densification and unregulated parking in the green areas, leads to a complete compromise of the meaning of the urban green system and quite logically ranks the city at the top of the negative rankings in recent years.Today, more than ever, Sofia needs a new, very well-thought-out regulatory framework with a long horizon and clear and pragmatic goals, in the context of modern challenges